Orientations pour l'évaluation des interventions visant la prévention des troubles musculo-squelettiques liés au travail - Fabien Coutarel; Nicole Vézina; Diane Berthelette; Agnès Aublet-Cuvelier; Alexis Descatha; Karine Chassaing; Yves Roquelaure; Catherine Ha (Perspectives Interdisciplinaires sur le Travail et la Santé)
The improvement of intervention practices is today an undeniable issue in the field of work-related musculoskeletal disorder (MSD) prevention. The development of knowledge about workplace interventions is therefore a research issue, which deals with the theme of intervention evaluation. International research in the MSD field focuses its work and recommendations mainly on the evaluation of the effects of interventions through the evolution in the state of the symptoms of the workers involved and/or the evolution in the exposures.In this article, we show first that this orientation assumes that a certain number of important conditions are associated, which are often difficult to associate and generally underestimated. We suggest that indicators relating to the work activity be considered, as well as employees’ margins of maneuver, as additional criteria in the evaluation, while emphasizing the necessity that work be carried out to make them operational.Second, we reiterate that the evaluation of the intervention’s effects is insufficient for developing knowledge about the intervention: this necessarily assumes the precise description of the intervention process and the consideration of its execution context.Finally, the discussion underlines the fact that, from our perspective, intervention evaluation is a project in itself, contributing directly to the transformation of the work.